2014
DOI: 10.1055/s-0034-1388372
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the RANK/RANKL genes and their effect on bone specific prognosis in breast cancer patients

Abstract: The receptor activator of NF-B (RANK) pathway is involved in bone health as well as breast cancer (BC) pathogenesis and progression. Whereas the therapeutic implication of this pathway is established for the treatment of osteoporosis and bone metastases, the application in adjuvant BC is currently investigated. As genetic variants in this pathway have been described to influence bone health, aim of this study was the prognostic relevance of genetic variants in RANK and RANKL. Single nucleotide polymorphisms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…However, different reports have also suggested that low levels of RANK and RANKL expression in the breast cancer tissue confer a poorer prognosis (42). In fact, the interaction of the RANKL/RANK pathway with regards to the bone-related outcome of patients breast cancer appears complex, and certain nucleotide polymorphisms in RANK and RANKL genes have been associated with a poorer bone metastasis-free survival (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, different reports have also suggested that low levels of RANK and RANKL expression in the breast cancer tissue confer a poorer prognosis (42). In fact, the interaction of the RANKL/RANK pathway with regards to the bone-related outcome of patients breast cancer appears complex, and certain nucleotide polymorphisms in RANK and RANKL genes have been associated with a poorer bone metastasis-free survival (43).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, no significant correlation was determined between all three groups with regard to RANK genotype and allele distributions (p>0.05). Hein et al reported no correlation between the prognosis of bone metastasis and RANK rs35211496 C/T polymorphism in breast cancer (23). It was concluded in the study of Santini et al on patients with breast cancer that RANK led to the development of bone metastasis in breast cancer (24).…”
Section: Discussionmentioning
confidence: 99%
“…The C variant was associated with susceptibility to Paget's disease of bone and knee osteoarthritis; conversely, it was found to have a protective role in hip osteoporotic fractures 26–28 . rs1805034 C was also a risk factor in esophageal cancer, but was not associated with risk for breast cancer 22,29,30 . These associations suggests that while the C allele seems to the causal variant, specific effects of the presence of the resultant valine‐including RANK protein may be different in various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We also checked for an association between RANKL and RANK SNPs, and serum concentration of the proapoptotic factor VEGF in a smaller group of patients (n = 32 [26][27][28] rs1805034 C was also a risk factor in esophageal cancer, but was not associated with risk for breast cancer. 22,29,30 These associations suggests that while the C allele seems to the causal variant, specific effects of the presence of the resultant valine-including RANK protein may be different in various diseases. rs1805034 C was also notably associated with age at menarche and postmenopausal osteoporosis in women, suggesting a female-specific effect.…”
Section: Associations Of Tnfsf11 Snps With Calcium Blood Levelsmentioning
confidence: 99%